Suppression of growth plate chondrocyte proliferation by corticosteroids - Klaus, Günter; Jux, Christian; Fernandez, P.; Rodriguez, J.; Himmele, Rainer; Mehls, Otto (Pediatric nephrology, 2000)
Growth depression is a side effect of high-dose glucocorticoid therapy in childhood. It is partially mediated by alterations of the somatotropic hormone axis and partially by direct local effects on growth plate chondrocytes. The mechanisms of interaction of corticosteroids and somatotropic and calciotropic hormones at the cellular level were recently investigated in more detail, using experimental models of primary cultures of growth plate chondrocytes. In proliferative chondrocytes, growth hormone (GH) and the calciotropic hormones parathyroid hormone (PTH) and 1,25-dihydroxyvitamin D [1α,25(OH)2D3] increase cell proliferation via stimulation of paracrine insulin-like growth factor-I (IGF-I) secretion. Corticosteroids decreased GH, and PTH or 1α,25(OH)2D3 stimulated cell growth in a dose-dependent manner. Corticosteroids in high doses reduced the expression of the GH receptor and type 1 IGF receptor. But the main antiproliferative molecular effect of corticosteroid was the reduction in basal and hormone-stimulated IGF-I secretion. The in vitro results are in accordance with the observation in animal experiments and in children treated with corticosteroids, demonstrating that the growth-depressing effect of corticosteroids can be compensated for by supraphysiological doses of GH or IGF-I.